Towards Parabiotic Partnerships for Access and Discovery: Leveraging Access to E-Content Within The Framework of Library Consortia In Zimbabwe - Chisita, Collence Tangaingenhamo; Rusero, Alexander Madanha (My University, 2016)
The age of intelligence presents library consortia in Zimbabwe with an opportunity to innovate, reinvent and re-profile in order to effectively disseminate research and scholarly communication as well as keep abreast of current technological development in ICTs. The survival of the library consortia is hinged upon renewal and reinvention through innovation and creativity and collaboration with National Research Networks to facilitate access to research and scholarly communication. This paper seeks to investigate the extent to which library consortia as part of the technological infrastructure can leverage strategic partnerships with NRENS for enhanced access and knowledge discovery. The paper will examine how partnerships with research networks and other key stakeholders can benefit resource sharing initiatives. It will explore the extent to which library consortia in Zimbabwe can use strategic partnerships to facilitate access to research and scholarly communication. The paper will find out the strategies that are in place to promote resource sharing, for example, collaboration between NRENS and library consortia and open access initiatives. The treatise will also seek to find out how library consortia can work with NRENS to enhance resource sharing and e-content licensing. The paper will examine how library consortia can utilize research networks to support self-determined learning (heutagogical) through provision for wider access to scholarly communication.
Keywords: Access to content; library consortia; partnerships and open access; NREN